Effect of residue retention, tillage options and timing of N application in rice-wheat cropping system (SAARC Journal of Agriculture, 2015)
A field experiment was conducted at the research farm of the Directorate of Wheat Research, Karnal (Haryana) during 2007-08 to 2009-10 with the objective to compare the whole basal and split application of nitrogen under different residue management and tillage options in rice-wheat cropping system. Combined analysis of data revealed that puddled transplanted rice produced maximum rice grain yield, straw yield, thousand grain weight and grains /panicle. Rice yield under zero tillage was decreased to the tune of 27.8% (with residue), 33.9% (without residue) and 45.3% (under permanent bed planting) as compared to puddled transplanted condition. Split application of nitrogen increased the rice grain yield to the extent of 4.7% with residue, 8.0% without residue and 10.2% under puddled transplanted condition as compared to whole basal N application. Pooled analysis under zero tillage condition, retention of rice residue enhanced the wheat grain yield 21.3% at zero N, 8.3% at 150 N (whole basal) and 5.4% at 150 N (three split) applications. Application of nitrogen in three split doses increased the wheat grain yield up to 9.6% without residue retention and 6.7% with rice residue retention condition as compared to whole basal N application. In nut shell, it can be said that adoption of zero tillage, residue retention and whole basal N application did not work well for rice whereas it was better for wheat in rice-wheat system.SAARC J. Agri., 13(1): 37-49 (2015)